Rapid T(1 )quantification based on 3D phase sensitive inversion recovery - Warntjes, Marcel JB (BioMed Central, 2010)
BACKGROUND: In Contrast Enhanced Magnetic Resonance Imaging fibrotic myocardium can be distinguished from healthy tissue using the difference in the longitudinal T(1 )relaxation after administration of Gadolinium, the so-called Late Gd Enhancement. The purpose of this work was to measure the myocardial absolute T(1 )post-Gd from a single breath-hold 3D Phase Sensitivity Inversion Recovery sequence (PSIR). Equations were derived to take the acquisition and saturation effects on the magnetization into account. METHODS: The accuracy of the method was investigated on phantoms and using simulations. The method was applied to a group of patients with suspected myocardial infarction where the absolute difference in relaxation of healthy and fibrotic myocardium was measured at about 15 minutes post-contrast. The evolution of the absolute R(1 )relaxation rate (1/T(1)) over time after contrast injection was followed for one patient and compared to T(1 )mapping using Look-Locker. Based on the T(1 )maps synthetic LGE images were reconstructed and compared to the conventional LGE images. RESULTS: The fitting algorithm is robust against variation in acquisition flip angle, the inversion delay time and cardiac arrhythmia. The observed relaxation rate of the myocardium is 1.2 s(-1), increasing to 6 - 7 s(-1 )after contrast injection and decreasing to 2 - 2.5 s(-1 )for healthy myocardium and to 3.5 - 4 s(-1 )for fibrotic myocardium. Synthesized images based on the T(1 )maps correspond very well to actual LGE images. CONCLUSIONS: The method provides a robust quantification of post-Gd T(1 )relaxation for a complete cardiac volume within a single breath-hold.